Impact of Pseudoexfoliative Syndrome on Effective Lens Position, Anterior Chamber Depth Changes, and Visual Outcome After Cataract Surgery - Müller M (Dove Medical Press, 2021)
Michael Müller, Katarzyna Pawlowicz, Myriam Böhm, Eva Hemkeppler, Christoph Lwowski, Lisa Hinzelmann, Mehdi Shajari, Thomas Kohnen Department of Ophthalmology, Goethe-University, Frankfurt, GermanyCorrespondence: Thomas KohnenDepartment of Ophthalmology, Goethe-University, Theodor-Stern-Kai 7, Frankfurt, 60590, GermanyTel +49 69 6301 3945Fax +49 69 6301 3893Email thomas.kohnen@kgu.dePurpose: To compare the effective lens position (ELP), anterior chamber depth (ACD) changes, and visual outcomes in patients with and without pseudoexfoliation syndrome (PEX) after cataract surgery.Design: Prospective, randomized, fellow-eye controlled clinical case series.Methods: This prospective comparative case series enrolled 56 eyes of 56 consecutive patients with (n = 28) or without PEX (n = 28) and clinically significant cataract who underwent standard phacoemulsification and were implanted with single-piece acrylic posterior chamber intraocular lenses (IOLs). The primary outcome parameters were the ACD referring to the distance between the corneal anterior surface and the lens anterior surface, which is an indicator of the postoperative axial position of the IOL (the so-called ELP) and distance corrected visual acuity (DCVA).Results: Before surgery, the ACD was 2.54 ± 0.42 mm in the PEX group and 2.53 ± 0.38 mm in the control group (p = 0.941). Postoperatively, the ACD was 4.29 ± 0.71 mm in the PEX group and 4.33 ± 0.72 mm in the normal group, respectively (p = 0.533). There was no significant difference in ACD changes between groups (PEX group: 1.75 ± 0.74 mm, control group: 1.81 ± 0.61 mm, p = 0.806) and DCVA pre- (p = 0.469) and postoperatively (PEX group: 0.11 ± 0.13 logMAR, control group: 0.09 ± 0.17 logMAR, p = 0.245) between groups.Conclusion: Preoperative and postoperative ACD, as an indicator of ELP, between PEX eyes and healthy eyes after cataract surgery showed no significant difference. Phacoemulsification induced similar changes in eyes with PEX compared to healthy eyes.Keywords: pseudoexfoliative syndrome, effective lens position, anterior chamber depth changes, cataract surgery